Perencanaan Pembangunan Ruang Publik untuk Kebutuhan Anak (Studi di Kecamatan Pare Kabupaten Kediri) - Pamungkas, Dwi Ratna (Jurnal Administrasi Publik, 2014)
Abstract: PLANNING FOR PUBLIC SPACE NEEDS FOR CHILDREN. (Studies in Subdistrict Pare Kediri). Development planning is now considered less attention to aspects of the child's needs, such as lack of recreational park for children. Children need a safe playground and convenient to develop aspects of the mind and body by focusing on physical, social, economic and environmental. To merencanaan development of public space as a playground facilities for children, the Government of Kediri Regency instrumental in providing a playground for children. This requires a spatial planning in accordance with the physical characteristics, social and cultural communities. Spatial planning is in conformity with the Regional Spatial Plan (Spatial) Kediri 2010-2030. The implementation includes the use of spatial planning, control of space and spatial planning of urban areas. Supervision spatial arrangement consisting of action monitoring, evaluation and reporting. The process of planning a public space for the needs of children has involved a range of stakeholders such as governments, private and public. There are construction (Green Open Space) green space of the park which has been synchronized with the city (Spatial Plan) Spatial. Keywords: Planning, Public Space, Children, Kediri Abstrak: PERENCANAAN PEMBANGUNAN RUANG PUBLIK UNTUK KEBUTUHAN ANAK (Studi di Kecamatan Pare Kabupaten Kediri). Perencanaan pembangunan sekarang ini dinilai kurang memperhatikan aspek kebutuhan anak, seperti minimnya taman rekreasi bagi anak-anak. Anak-anak membutuhkan taman bermain yang aman dan nyaman untuk mengembangkan aspek jiwa dan raga dengan memperhatikan aspek fisik, sosial, ekonomi dan lingkungan. Untuk merencanaan pembangunan ruang publik sebagai sarana taman bermain bagi anak-anak, Pemerintah Kabupaten Kediri berperan penting dalam penyediaan taman bermain bagi anak-anak. Untuk itu diperlukan suatu perencanaan penataan ruang yang sesuai dengan karakteristik fisik, sosial dan budaya masyarakat setempat. Â Perencanaan tata ruang wilayah sudah sesuai dengan Rencana Tata Ruang Wilayah (RTRW) Kabupaten Kediri 2010-2030. Pelaksanaan penataan ruang meliputi pemanfaatan, pengendalian ruang dan penataan ruang kawasan perkotaan. Pengawasan penataan ruang terdiri atas tindakan pemantauan, evaluasi dan pelaporan. Proses perencanaan pembangunan ruang publik untuk kebutuhan anak telah melibatkan berbagai pihak seperti pemerintah, swasta dan masyarakat. Terdapat pembangunan (Ruang Terbuka Hijau) RTH berupa taman kota yang telah tersinkron dengan (Rencana Tata Ruang Wilayah) RTRW. Kata Kunci: Perencanaan, Ruang Publik, Anak, Kediri